RESEARCH OF THE OBJECT OF AUTOMATIC CONTROL OF TECHNOLOGICAL PROCESSES (British Journal of Global Ecology and Sustainable Development, 2022)
This article covers the issues of improving the methodology for researching the adaptability of the object model through automatic control of technological processes.